Microstructural control of corrosion behavior of Cu–3Fe–5Zn alloy via annealing - Yanggang Wang; Yanbin Jiang; Zhou Li (Journal of Materials Research and Technology)
This study systematically analyzed the corrosion behavior of the Cu–3Fe–5Zn alloy at various annealing temperatures, focusing on the influencing factors and mechanisms of intragranular, intergranular, and Cu/Fe interfacial corrosion. Combing experimental data with the Lifshitz-Slyozov-Wagner (LSW) theory, the diffusion coefficients of Fe at 650 °C and 800 °C were found to 7.62 × 10−17 m2/s and 3.95 × 10−15 m2/s, respectively. The coarsening rate at 800 °C (1.06 × 10−26 m3/s) was significantly higher than at 650 °C (7.35 × 10−29 m3/s), indicating that higher annealing temperatures promote Fe precipitate coarsening and reduce the number of precipitates, thereby lowering the Cu/Fe interfacial corrosion rate. Additionally, the intergranular corrosion was closely related to grain boundary connectivity. As the annealing temperature increased, the proportion of coincidence site lattice (CSL) grain boundaries increased, reducing the grain boundary connectivity, which in turn decreased the corrosion and Cu ion release rates. In particular, when the annealing temperature exceeded 700 °C, the CSL boundaries effectively disrupted the grain boundary network, significantly inhibiting intergranular corrosion. Finally, an increased annealing temperature decreased the dislocation density, thereby mitigating intragranular corrosion. The result of this study provides theoretical support for controlling the ion release rate of the Cu–3Fe–5Zn alloy.